ADP‐heptose is a newly identified pathogen‐associated molecular pattern of Shigella flexneri. (19th November 2018) - García‐Weber, Diego; Dangeard, Anne‐Sophie; Cornil, Johan; Thai, Linda; Rytter, Héloïse; Zamyatina, Alla; Mulard, Laurence A; Arrieumerlou, Cécile
Abstract: During an infection, the detection of pathogens is mediated through the interactions between pathogen‐associated molecular patterns (PAMPs) and pathogen recognition receptors. β‐Heptose 1, 7‐bisphosphate (βHBP), an intermediate of the lipopolysaccharide (LPS) biosynthesis pathway, was recently identified as a bacterial PAMP. It was reported that βHBP sensing leads to oligomerization of TIFA proteins, a mechanism controlling NF‐κB activation and pro‐inflammatory gene expression. Here, we compare the ability of chemically synthesized βHBP and Shigella flexneri lysate to induce TIFA oligomerization in epithelial cells. We find that, unlike bacterial lysate, βHBP fails to initiate rapid TIFA oligomerization. It only induces delayed signaling, suggesting that βHBP must be processed intracellularly to trigger inflammation. Gene deletion and complementation analysis of the LPS biosynthesis pathway revealed that ADP‐heptose is the bacterial metabolite responsible for rapid TIFA oligomerization. ADP‐heptose sensing occurs down to 10 −10 M. During S. flexneri infection, it results in cytokine production, a process dependent on the kinase ALPK1. Altogether, our results rule out a major role of βHBP in S. flexneri infection and identify ADP‐heptose as a new bacterial PAMP. Synopsis: ADP‐heptose is a newly identified pathogen‐associated molecular pattern of Shigella flexneri . Unlike βHBP, ADP‐heptose triggers rapid ALPK1‐dependent TIFA oligomerization leading to subsequent inflammatory cytokine production. During Shigella flexneri infection, recognition of bacterial ADP‐heptose elicits rapid oligomerization of TIFA and the production of inflammatory cytokines. ALPK1 silencing abrogates ADP‐heptose‐induced TIFA oligomerization and cytokine production. Abstract : ADP‐heptose is a newly identified pathogen‐associated molecular pattern of Shigella flexneri . Unlike βHBP, ADP‐heptose triggers rapid ALPK1‐dependent TIFA oligomerization leading to subsequent inflammatory cytokine production.